Measuring the Impact of Culturally Relevant Literature and Inquiry-based Activities on STEM Identity in Children - Karen M. Collier; Wayne A. Hickman; Elizabeth A. VanDeusen; Katherine A. Barker (Advanced Journal of STEM Education, 2026)
Out-of-school activities have the potential to broaden participation in STEM, especially for groups with less access to school-based opportunities. This mixed-methods, cross-sectional study aimed to engage families in STEM activities and provide culturally relevant books at a community-based STEM Family Night (N = 9) and a university-based summer program (N = 21). The objective of the study was to measure the project's impact on individuals’ STEM identity and alignment with social justice constructs. Participants were invited to take two surveys: 1) Culturally Relevant STEM and 2) STEM Identity. A Justice-centered STEM Framework (JCSF) served as the theoretical framework, and both surveys included Likert-scale and open-response items. The research questions guiding this project include: 1) What patterns are seen in student participation across the two programs? 2) Do the survey responses support the JCSF and STEM identity, and what differences in survey responses exist between programs? 3) Do the open-response items reflect the constructs of JCSF? Data analyses included item and survey means, t-tests, and thematic coding. Findings revealed significantly higher scores on the Culturally Relevant STEM survey mean and on one item related to confidence in STEM for the summer program; commitment to community and inspiring were the most common themes. The highest-scoring subscales on the STEM Identity survey were recognition by others and self-recognition, and the most common themes identified were authentic STEM and enjoyment and engagement. This study supports the implementation of informal STEM events and the positive impact of culturally relevant books on individuals’ STEM Identity.